Does Month of Birth Affect Speed and Quality of Transition from School to Work? - Stijn Baert; Luca Fumarco; Levi Halewyck; Eline Moens; Alessandro Vandromme (De Economist, 2025)
This study estimates the impact of relative age (i.e., the difference in classmates' ages) on both the speed and quality of individuals' transition from education to the labour market, and investigates whether and how this impact passes through characteristics of students' educational careers—topics that have been largely overlooked in prior work. We use rich data pertaining to schooling and to labour market outcomes one year after graduation to conduct instrumental variables analyses. We find that a one-year increase in relative age increases the likelihood of (i) being employed then by 3.5 percentage points (baseline 91.2%), (ii) having a permanent contract by 5.1 percentage points (baseline 42.6%), and (iii) having full-time employment by 6.5 percentage points (baseline 79.5%). These relative age effects are partly mediated by intermediate outcomes such as having had a schooling delay at the age of sixteen or taking on student jobs. The final mediator is particularly notable as no earlier studies examined relative age effects on student employment.
Keywords: I21; J23; J24; J6; 330; Relative age; School starting age; Labour market transition